2007
DOI: 10.3349/ymj.2007.48.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Factors Affecting the Success of Weight Reduction Programs

Abstract: Obesity is a risk factor for numerous health problems. Behavior therapy is important for obesity treatment. The aim of the present study was to identify the parameters that are associated with successful weight reduction. A database of 123 subjects who underwent weight reduction programs at the Center for Health Promotion, Samsung Medical Center from June 2001 through November 2004 was retrospectively analyzed. The goal of the program was to reduce the body weight by more than 5% during the follow-up period. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Even a single visit to a dietitian had a significant effect on the likelihood to succeed in achieving and maintaining weight reduction. This finding is in line with previous studies, which found visits to a dietitian as a significant predictor for weight loss and maintenance in structured weight loss programs . It should be emphasised that our study is unique in showing this effect also in a community setting.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Even a single visit to a dietitian had a significant effect on the likelihood to succeed in achieving and maintaining weight reduction. This finding is in line with previous studies, which found visits to a dietitian as a significant predictor for weight loss and maintenance in structured weight loss programs . It should be emphasised that our study is unique in showing this effect also in a community setting.…”
Section: Discussionsupporting
confidence: 93%
“…A possible explanation is that when subjects lose large amount of fat they experience favourable changes in their body shape and motivation, and are thus more motivated to maintain weight . The literature, however, is inconsistent regarding this issue: similar to our results, many studies reported higher baseline BMI as a significant predictor of success in weight reduction and maintenance during short and long follow up periods . However, it was also reported that at extreme baseline BMI (above 35) the probability of weight loss and maintenance success declines…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations